2014
DOI: 10.1017/s1041610214001604
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study: comparative research of social functioning, circadian rhythm parameters, and cognitive function among institutional inpatients, and outpatients with chronic schizophrenia and healthy elderly people

Abstract: The characteristics of circadian rhythm and cognition function in the inpatients with chronic schizophrenia appear distinct from those in the outpatients and the healthy elderly people. Circadian rhythm and cognition function in the patients with chronic schizophrenia may, in part, be affected by different living environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Excluding 3 schizophrenia studies 36–38 with mean participant age >50 resulted in acrophase reaching statistical significance in this group (SMD [95% CI] = 0.47 [0.05, 0.89], P < .05), but did not alter outcomes for the other variables. Excluding the 2 bipolar disorder studies that included a subset of participants not meeting age 39 or remission criteria 58 did not significantly alter mean differences in sleep and circadian parameters, except for sleep efficiency in the bipolar disorder group no longer reaching statistical significance.…”
Section: Resultsmentioning
confidence: 94%
“…Excluding 3 schizophrenia studies 36–38 with mean participant age >50 resulted in acrophase reaching statistical significance in this group (SMD [95% CI] = 0.47 [0.05, 0.89], P < .05), but did not alter outcomes for the other variables. Excluding the 2 bipolar disorder studies that included a subset of participants not meeting age 39 or remission criteria 58 did not significantly alter mean differences in sleep and circadian parameters, except for sleep efficiency in the bipolar disorder group no longer reaching statistical significance.…”
Section: Resultsmentioning
confidence: 94%
“…Changes in circadian rhythms in patients with chronic schizophrenia can have a significant impact on their overall functioning and their ability to maintain adequate social lives. Among these changes is less exposure to daylight, which contributes to the reduced circadian rhythm synchronization (Kume et al, 2015). Wulff et al (2012) documented abnormalities in sleep-wake cycles and melatonin levels in patients with schizophrenia who had subjective sleep problems.…”
Section: Discussionmentioning
confidence: 99%
“…Another finding in this study is that comorbid CRSWD may be associated with psychosocial functioning. One study demonstrated no correlation between circadian rhythm and social dysfunction in patients with schizophrenia, but it focused on older adult patients and included both inpatients and outpatients [52]. To the best of our knowledge, our study is the first to focus on the relationship between CRSWD and psychosocial functioning in outpatients with schizophrenia across a wide age range.…”
Section: Discussionmentioning
confidence: 90%